1998
DOI: 10.1142/s0218396x98000107
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Geoacoustic Inversion from Sparse Data Using Genetic Algorithms

Abstract: Matched-field acoustic inversion techniques were investigated using data from sparsely populated vertical receiving arrays and a single receiver element. The purpose of considering sparse data sets is to investigate, under simulation, the feasibility of reducing the number and complexity of acoustic measurements needed for geoacoustic inversion. The entire bandwidth of the 1997 Geoacoustic Inversion Workshop provided data (25–500 Hz) was used which compensates for the lack of spatial information when a limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Matched field inversion ͑MFI͒ is an effective geoacoustic inversion technique that has been benchmarked with simulated data, [1][2][3][4][5][6][7][8][9][10][11] and applied to extract simple but physically meaningful geoacoustic models for several different experimental environments. [12][13][14][15][16][17][18] Point estimation by optimization algorithms and appraisal analysis based on Bayesian theory are the two major approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Matched field inversion ͑MFI͒ is an effective geoacoustic inversion technique that has been benchmarked with simulated data, [1][2][3][4][5][6][7][8][9][10][11] and applied to extract simple but physically meaningful geoacoustic models for several different experimental environments. [12][13][14][15][16][17][18] Point estimation by optimization algorithms and appraisal analysis based on Bayesian theory are the two major approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Justification for the single sediment layer assumption is obtained from literature. 12 Here it was found that inversions of synthetic data, calculated for a multi-layer bottom, and using a two-layer model for the forward calculations, resulted in properties of the two-layer bottom that fitted the properties of the actual multi-layer model reasonably well.…”
Section: The Acoustic Problemmentioning
confidence: 86%
“…Some justification for the two layer approach can be obtained from olXn S to a geo-acoustic benchmarking workshop case [26,27]. In that benchmark case MFP inversions of simulated data, using a two layer model, reasonably fit tlL properties of a multi-layer bottom in a least-squared sense.…”
Section: The Forward Acoustic Propagationmentioning
confidence: 99%